Effect of short-term creatine monohydrate supplementation on indirect markers of cellular damage in young soccer players - Atashak, S.; Jafari, A. (Science & Sports, 2012)
Purpose: In recent years, creatine (Cr) supplementation has received great attention in both popular and scientific media. Nevertheless, there is anecdotal information on the side effects of this supplement. Hence, we hypothesized that Cr monohydrate (CrM) loading would induce increase in serum enzymes activity as indirect markers of cellular damage. Therefore, the present study was conducted to identify the effect of short-term Cr supplementation on serum lactate dehydrogenase (LDH), creatine phosphokinase (CK), and myocardial CK isoform (CKMB) in young male soccer players. Methods: Eighteen volunteer young male soccer players in a randomized and double-blind design were divided into two equal groups (Cr & Placebo groups). Creatine (CrM) group was ingested Cr supplementation (0.3 g/kg/d for 7 days), but placebo group (Pl) was not took any supplements. All subjects were participated in circuit weight training (eight exercises, three sets, 15 repetitions, and 60% one repetition maximum [1RM]). To identify enzymes activity (IU/L), venous blood samples were obtained before Cr loading and 24 h after last session of weight training, Moreover, VO2max each of subjects were obtained with 20 m Shuttle Run test. Data were expressed as mean (±SD) and analyzed by paired and independent t-tests using SPSS15 at P ? 0.05. Results: The modest elevation of LDH activity in both groups were not significant following the short-term Cr supplementation, whereas, mean and changes range of CK (P = 0.0004, tCK = 5.13) and CKMB (P < 0.05, tCKMB = 2.10) activities in CrM group were significantly higher than in Pl group (P < 0.05). Conclusion: The present results suggest that serum CK and CKMB activity as indirect markers of cellular damage increases by the oral short-term CrM supplementation in young male soccer players. Therefore, it can be concluded that CrM loading probably have significant adverse effects on serum indirect markers of cellular damage. Nevertheless, more research will be needed to determine effect of the short and long-term Cr supplementation on the other indirect markers of cellular damages in the future.